Question

3. a. \( 2^{5} \times 2^{-3} \) b. \( 4^{3} \div 4^{-4} \) c. \( 2 a^{-2} \times 3 a^{3} \times a^{0} \)

Ask by Fernandez Gonzalez. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a. 4 b. 16384 c. 6a

Solution

Simplify the expression by following steps: - step0: Solution: \(2a^{-2}\times 3a^{3}\times a^{0}\) - step1: Evaluate the power: \(2a^{-2}\times 3a^{3}\times 1\) - step2: Rewrite the expression: \(2a^{-2}\times 3a^{3}\) - step3: Multiply the terms: \(6a^{-2}\times a^{3}\) - step4: Multiply the terms: \(6a^{-2+3}\) - step5: Add the numbers: \(6a\) Calculate or simplify the expression \( 4^{3} / 4^{-4} \). Calculate the value by following steps: - step0: Calculate: \(\frac{4^{3}}{4^{-4}}\) - step1: Multiply by \(a^{-n}:\) \(4^{3}\times 4^{4}\) - step2: Multiply: \(4^{3+4}\) - step3: Add the numbers: \(4^{7}\) - step4: Evaluate the power: \(16384\) Calculate or simplify the expression \( 2^{5} * 2^{-3} \). Calculate the value by following steps: - step0: Calculate: \(2^{5}\times 2^{-3}\) - step1: Multiply: \(2^{5-3}\) - step2: Subtract the numbers: \(2^{2}\) - step3: Evaluate the power: \(4\) Here are the solutions for each part of the problem: ### a. \( 2^{5} \times 2^{-3} \) To simplify this expression, we can use the property of exponents that states \( a^{m} \times a^{n} = a^{m+n} \). \[ 2^{5} \times 2^{-3} = 2^{5 + (-3)} = 2^{2} = 4 \] **Result:** \( 4 \) --- ### b. \( 4^{3} \div 4^{-4} \) For division of exponents, we use the property \( a^{m} \div a^{n} = a^{m-n} \). \[ 4^{3} \div 4^{-4} = 4^{3 - (-4)} = 4^{3 + 4} = 4^{7} \] Calculating \( 4^{7} \): \[ 4^{7} = (2^{2})^{7} = 2^{14} = 16384 \] **Result:** \( 16384 \) --- ### c. \( 2 a^{-2} \times 3 a^{3} \times a^{0} \) Using the properties of exponents, we can simplify this expression step by step: 1. Combine the coefficients: \( 2 \times 3 = 6 \) 2. Combine the \( a \) terms: \( a^{-2} \times a^{3} \times a^{0} = a^{-2 + 3 + 0} = a^{1} = a \) Putting it all together: \[ 2 a^{-2} \times 3 a^{3} \times a^{0} = 6 a \] **Result:** \( 6a \) --- ### Summary of Results: - a. \( 4 \) - b. \( 16384 \) - c. \( 6a \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve \( 2^{5} \times 2^{-3} \), we combine the exponents since the bases are the same. This gives us \( 2^{5 + (-3)} = 2^{2} = 4 \). For \( 4^{3} \div 4^{-4} \), remember that dividing means subtracting exponents. So, we have \( 4^{3 - (-4)} = 4^{3 + 4} = 4^{7} = 16384 \). For \( 2 a^{-2} \times 3 a^{3} \times a^{0} \), we first use the associative property and multiply the coefficients: \( 2 \times 3 = 6 \). Then we combine the exponents: \( a^{-2} \times a^{3} \times a^{0} = a^{-2 + 3 + 0} = a^{1} = a \). Thus, the final answer is \( 6a \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy